CHANGES IN ESTERASE AND SUPEROXIDE DISMUTASE ISOZYMES DURING IN VITRO MORPHOGENESIS IN PLANTAGO OVATA FORSSK. - PRAMANIK, S.
Callus cultures were established from hypocotyl explants of Plantago ovata in Murashige and Skoog`s medium supplemented with 2,4-DlKinetin and NAAIBA combinations. Calluses growing on NAAIBA (0.4 mg 1-1 each) regenerated into plantlets after the second subculture when transferred to media containing IAA (0.2 mg 1-1) and BA (5 mg 1-1). Shoot tip multiplication was carried out in the same media with IAA and BA. Tissue samples from calluses, regenerating plantlets and multiplying shoot tips grown in vitro were extracted with protein extraction buffer and subjected to esterase and superoxide dismutase isozyme analysis. The calluses however, showed a uniform banding in esterase even when grown on different hormone combinations. The multiplying shootlets showed two new bands which were not found in either the control or the regenerating plants. A new band was also found in the multiplying shootlets when analysed for superoxide dismutase. It is postulated that those new enzyme forms which arise